Crossing the Hudson : historic bridges and tunnels of the river - Wolf, Donald E., 1927- (Rivergate Books, 2010)
Crossing the Hudson reveals the often multileveled stories of the river's bridges and tunnels, from timber arch and truss bridges on stone piers to long-span suspension and cantilevered bridges, railroad tunnels, and improvements in iron and steel technology, providing a history of where, why, when, and how these structures were built; the social, political, and commercial forces that influenced decisions to erect them; the personalities of the planners and builders; the unique connection between builder and bridge; and the design and construction techniques that turned mythical goals in.